Trigonometric widths of the classes $B_{p,θ}^ r$ of functions of many variables in the space $L_q$ - Romanyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We obtain estimates exact in order for the trigonometric widths of the Besov classes $B_{p,θ}^ r$ of periodic functions of many variables in the space $L_q$ for $1 ≤ p ≤ 2 < q < p/(p - 1)$.